Drug dependence is not addiction—and it matters - Maia Szalavitz; Khary K. Rigg; Sarah E. Wakeman (Annals of Medicine)
Accurately identifying persons with addiction is critically important for effectively targeting treatment and harm reduction interventions. Misdiagnosis of addictive disorders can lead to a cascade of negative outcomes, including stigma, discontinuation of needed medications, undue scrutiny of both patients and physicians, and even criminal consequences. A recent study raises significant concerns about the accuracy of diagnosis code data, likely rooted in confusingly-worded International Classification of Diseases (ICD)-9 and ICD-10 codes and a general misunderstanding of the difference between addiction and physiologic dependence. It is hardly surprising that physicians frequently mislabel patients when the ICD terms used to code for addiction are themselves misleading. ICD codes have not been updated to reflect current understanding of addiction, unlike those in the DSM-5. To explore this issue further, this commentary briefly discusses new information regarding coding data inaccuracies, how coding inaccuracies can lead to misdiagnosis, and the dangers of conflating “addiction” with “dependence.” The commentary concludes with a call for the ICD to update their codes to reflect current understanding of addiction.Key messagesIt is not surprising that physicians frequently conflate patients with “addiction” and “dependence” when the ICD terms used to code for addiction are themselves misleading.ICD codes have not been updated to reflect what we know about the nature of addiction, unlike those in the DSM-5.This commentary calls for the ICD to update their codes to reflect current understanding of addiction.